THE CONCEPT OF REVELATION GUIDING SCIENCE AS A SCIENTIFIC PARADIGM UIN SUNAN GUNUNG DJATI BANDUNG - Aang Mahyani; Nanat Fatah Natsir; Erni Haryanti (Pusat Penerbitan Universitas (P2U) Unisba, 2021)
In 2008, Wahyu Menandu Ilmu was used as the basis for formulating the vision of UIN Sunan Gunung Djati Bandung and in 2015, editorially it became part of the vision of UIN Sunan Gunung Djati Bandung. The application of the concept of Wahyu Guiding Science must be contained in the curriculum of the study program at UIN Sunan Gunung Djati Bandung and become an identity that is not shared by other universities and in 2016-2017 the book trilogy Revelation Guides Science (Masterplan KK-WMI) was compiled. The epistemology of non-dichotomous Islamic scholarship, UIN Sunan Gunung Djati Bandung expands its mandate by not only developing Islamic Religion but also studying Natural Sciences, Social Sciences and Humanities (Humanities Sciences).